Development of Cultural Tourism in Kutu Wetan Village with Community Involvement to Increase Local Wealth - Amin, Grace; Rahmiati, Filda; Goenadhi, Felix; Widyanto, Hanif Adinugroho (AIBPM Publisher, 2023)
One of the most important parts of the tourist industry all around the world is cultural tourism. Through the utilization of cultural tourism, tourism villages are able to utilize it as a source of income for the community. This study's objective was to investigate and evaluate several approaches to the promotion of cultural tourism in Kutu Wetan Village, Ponorogo. Participatory observation and in-depth interviews were utilized as components of a qualitative data collecting approach for the purpose of gathering the aforementioned information. The research team conducted interviews with the chief of Kutu Wetan Village, members of the surrounding communities, and officials from the regional administration. In addition, researchers participate in cultural events in Ponorogo, such as the Reog Ponorogo Festival, in order to gauge the community's level of interest in maintaining its cultural tourism and preserve its traditions. The findings demonstrated that cultural tourism plays an important role among the many goods and services offered by the tourist industry. On the other hand, there is still a need to improve support from both the government and the community through promoting involvement in the development of tourist initiatives. The growing sense of pride that local people have in their culture can have an effect on the competitive advantage that sustainable tourism enjoys.